COOLING OF GRANITIC ROCKS IN THE PALU REGION, MIDDLE SULAWESI: ZIRCON AND APATITE FISSION TRACK CONSTRAINTS - Sam Permanadewi; Baharuddin Baharuddin (Pusat Survei Geologi, 2012)
Zircon and apatite fission track analysis has been employed to constrain a cooling episode of the Oligocene-Miocene granitic sequences in the Palu region, Middle Sulawesi. A fission track dating from five outcrops resulted in zircon ages ranging between 9.5±0.5 Ma and 29.5±2.1 Ma. These ages may represent the onset of crystallisation during magmatic emplacement. This interpretation is consistent with the corresponding K/Ar ages ranging between 8.6 Ma for biotite and 31 Ma for feldspar. All but one sample show apatite fission track ages younger than zircon ages. The apatite fission track ages range between 6.2±1.3 Ma and 29.3±2.5 Ma. Importantly, the oldest zircon and apatite crystals separated from the rock sample derived from pluton in the southern section suggest that the host sequence has not undergone a further cooling event since crystallisation in the Oligocene. However, the remaining apatite fission track ages from rock successions in the northern sector of the studied region reveal an episode of post-crystallisation rapid cooling of the Oligocene granitic pluton, possibly due to local-scale uplift in response to overthrust in the late Miocene.Keywords: cooling, fission track, granitic pluton, Sulawesi